Health professionals ethical and legal liability on patient’s inadequate clarification in order to obtain free and informed consent - Serra, Mônica da Costa [UNESP]; Melhen, José Eduardo; Melani, Rodolfo Francisco Haltenhoff; Fernandes, Clemente Maia da Silva [UNESP] (My University, 2010)
It is required that patients are provided information about therapeutic possibilities, showing the risks, benefits, prognosis and costs of each possible and indicated alternative. This is an ethical and legal resolution. However, health professionals possess the clinical/technical/scientific knowledge and determine what information will be (or not) provided. The patient in question decides to undergo a treatment, providing his/her free and informed consent on the basis of the data presented. Unfortunately, some professionals may not provide all the information necessary for making an informed decision or, after obtaining the consent of the patient, may provide him information that causes the patient to give up on the treatment initially accepted. Such information, if relevant, and not a supervening fact, should have been provided initially. However, the information may not be entirely true, and bring the patient, for instance, to decide based on inadequately presented risks. The craniofacial rehabilitation of the temporomandibular joint (TMJ) by means of TMJ prosthesis, is indicated in many situations. Often, patients in need of such prostheses have aesthetic and functional problems and the rehabilitation expectations run high. This work presents a case and discusses ethical and legal issues, including the liability of partial and inadequate information to a patient.